This one is going to i
hope this helped
Answer:
The equation of line is:
![8x-9y=-23](https://tex.z-dn.net/?f=8x-9y%3D-23)
Step-by-step explanation:
We are given that a graph is a that passes through two points:
and ![(\dfrac{1}{2},3)](https://tex.z-dn.net/?f=%28%5Cdfrac%7B1%7D%7B2%7D%2C3%29)
We know that the equation of line passing through two points:
and
is given by:
![y-b=\dfrac{d-b}{b-a}\times (x-a)](https://tex.z-dn.net/?f=y-b%3D%5Cdfrac%7Bd-b%7D%7Bb-a%7D%5Ctimes%20%28x-a%29)
Here we have:
and ![(c,d)=(\dfrac{1}{2},3)](https://tex.z-dn.net/?f=%28c%2Cd%29%3D%28%5Cdfrac%7B1%7D%7B2%7D%2C3%29)
Hence, the equation of line is:
![y-(-1)=\dfrac{3-(-1)}{\dfrac{1}{2}-(-4)}\times (x-(-4))\\\\y+1=\dfrac{3+1}{\dfrac{1}{2}+4}\times (x+4)\\\\y+1=\dfrac{4}{\dfrac{9}{2}}\times (x+4)\\\\y+1=\dfrac{4\times 2}{9}\times (x+4)\\\\y+1=\dfrac{8}{9}\times (x+4)\\\\9\times (y+1)=8\times (x+4)\\\\9y+9=8x+8\times 4\\\\9y+9=8x+32\\\\8x-9y=9-32\\\\8x-9y=-23](https://tex.z-dn.net/?f=y-%28-1%29%3D%5Cdfrac%7B3-%28-1%29%7D%7B%5Cdfrac%7B1%7D%7B2%7D-%28-4%29%7D%5Ctimes%20%28x-%28-4%29%29%5C%5C%5C%5Cy%2B1%3D%5Cdfrac%7B3%2B1%7D%7B%5Cdfrac%7B1%7D%7B2%7D%2B4%7D%5Ctimes%20%28x%2B4%29%5C%5C%5C%5Cy%2B1%3D%5Cdfrac%7B4%7D%7B%5Cdfrac%7B9%7D%7B2%7D%7D%5Ctimes%20%28x%2B4%29%5C%5C%5C%5Cy%2B1%3D%5Cdfrac%7B4%5Ctimes%202%7D%7B9%7D%5Ctimes%20%28x%2B4%29%5C%5C%5C%5Cy%2B1%3D%5Cdfrac%7B8%7D%7B9%7D%5Ctimes%20%28x%2B4%29%5C%5C%5C%5C9%5Ctimes%20%28y%2B1%29%3D8%5Ctimes%20%28x%2B4%29%5C%5C%5C%5C9y%2B9%3D8x%2B8%5Ctimes%204%5C%5C%5C%5C9y%2B9%3D8x%2B32%5C%5C%5C%5C8x-9y%3D9-32%5C%5C%5C%5C8x-9y%3D-23)
Hence the equation of line is:
![8x-9y=-23](https://tex.z-dn.net/?f=8x-9y%3D-23)